2006
DOI: 10.1002/pen.20548
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency proximity heating for injection molding applications

Abstract: High‐frequency proximity heating was used to rapidly heat injection molds. The principle is based on the proximity effect between a pair of mold inserts facing each other with a small gap and forming a high‐frequency electric loop. Because of the proximity effect, the high‐frequency current will flow at the inner surfaces of the facing pair, thus selectively heating the mold surface. With this method, the electrical insulation layer beneath the mold surface can be eliminated, resulting in a mold insert made of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 8 publications
0
65
0
Order By: Relevance
“…Mold surface heating, such as induction heating [10][11][12], high-frequency proximity heating [13,14], and gas-assisted mold temperature control (GMTC) [15,16], can provide sufficient heating rates without significant increases in cycle time. In recent years, we have conducted systematic study of mold surface heating and mold surface localization heating of the processing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Mold surface heating, such as induction heating [10][11][12], high-frequency proximity heating [13,14], and gas-assisted mold temperature control (GMTC) [15,16], can provide sufficient heating rates without significant increases in cycle time. In recent years, we have conducted systematic study of mold surface heating and mold surface localization heating of the processing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations 27,28,39 indicated that, with a proper design, a mold with a low thermal mass can deliver a rapid temperature rise of 100…”
Section: Mold With Low Thermal Massmentioning
confidence: 99%
“…Examples are low thermal inertia molding, 4,5 variotherm injection molding, 9−12 momentary mold surface heating process, 13−17 rapid thermal response molding, 18−20 rapid thermal processing, 21 and dynamic mold surface temperature control 22−25 . A number of innovative approaches for rapidly heating only the surface portion of the mold have been presented, including methods such as resistive heating of a thin conductive layer, 26−30 convective heating using hot fluid, 31−34 heating using condensing vapor, 35 induction heating, 9−12,22−25,36−38 high-frequency proximity heating, 39,40 infrared heating, 21,41−47 heating and cooling using a volume-controlled variable conductance heat pipe, 48,49 heating and cooling using thermoelectric Peltier modules, 2,50 passive heating by the incoming polymer, 5,51−61 microwave heating, 62,63 contact heating, 64,65 flame heating, 13−17 etc. Despite the large body of literature available, mold rapid heating and cooling does not represent a well-developed area of expertise.…”
mentioning
confidence: 99%
“…Adequate isolation of the heating elements from the mould base will favor the cycle time reduction and increase economic efficiency of the microinjection molding process (Gornik, 2004). Yao et al (2006) have implemented a local heating of the mould insert by highfrequency current. Unlike the conventional resistive techniques, mould surface heating rate can reach 40°C/s with an apparent heating power of 93 W/cm 2 , while only the local electrical insulation of the mould insert is necessary.…”
Section: Wwwintechopencommentioning
confidence: 99%